Pengaruh lama perendaman dan persentase carboxymethyl cellulose (CMC) terhadap karakteristik susu kecambah kedelai (Glysine max (L.) Merr.) - Lailatul Rizkiyah; Deny Utomo (Program Studi Ilmu dan Teknologi Pangan, Universitas Yudharta, Pasuruan, 2020)
Soy-based drinks are an alternative source of high-quality vegetable protein and have almost the same content as cow's milk but do not contain lactose which can cause digestive problems in some people (lactose intolerance). Nutrition value and quality in legumes will be better after going through the germination process. This study aims to determine the effect of soybean seed soaking time and the percentage of stabilizer Carboxymethyl Cellulose (CMC) on the best chemical, physical and olganoleptic quality in soybean sprouts milk. The method used in the study of soybean sprouts milk is Random Factorial Design (RCBD) which consists of 2 factors: soaking time (4 hours, 8 hours and 12 hours) and the percentage ofstabilizers Carboxymethyl Cellulose (CMC) (0.4% and 0,6%). Each treatment was repeated 3 times so 18 trials were obtained. The tests included chemical tests including protein content and antioxidant activity, physical including viscosity and organoleptics including color, the flavor, texture and taste. Analysis of chemical and physical content data is done using the Minitab application to search fordata Analysis of Variance and to determine the notation using the Tukey Method. While the organoleptic test uses the Friedman method and to find the best treatment using the Effectiveness Index. The best research results on soybean sprouts milk on chemical, physical and organoleptic content were found in the P1C1 treatment (4 hours immersion time and 0,4% CMC percentage) with protein analysis results with a value of 4.97, antioxidant activity with a value of 45.75, viscosity with a value of 19.73, color with a value of 35.33 (likes), the flavor with a value of 3.50 (somewhat like), texture with a value of 3.20 (somewhat like) and taste with a value of 3.63 (like).